Destructive effect of combat stress on the emotional sphere of the military personality - Liashch , Oksana; Yatsiuk , Mariia (Psychological Prospects Journal, 2021)
Purpose. The purpose of the article is to establish the destructive effects of combat stress on the emotional sphere of the military. Methods. In accordance with the purpose of the study used content analysis of the conversation, methods for determining the level of stress L. Reeder, PHQ-9 scale of self-assessment of depression, Taylor anxiety scale, methods of mathematical statistics. Results. The article considers the problem of the impact of combat stress on the emotional sphere of the military. It is noted that the main reaction of a serviceman to combat events is combat stress, the difference of which is the presence of stress factors in the combat situation. It is specified that combat stress is understood as a multilevel process of adaptive activity of the human body in a combat situation, accompanied by the actualization of the mechanisms of reactive self-regulation and the consolidation of specific adaptive psychophysiological changes. The results of the study indicate that the negative mental states that occur in servicemen during the performance of tasks dangerous to health and life, when returning from combat, are manifested in an exacerbation of honor, dignity and justice, increased reactions of uncontrolled aggression, anxiety, conflicts that dramatically complicate the process of readaptation of demobilized servicemen and certainly require psychological correction. The results of the study indicate that long-term traumatic factors of the combat situation have a destructive effect on the emotional sphere of the military, and due to personal characteristics, many demobilized violate the regulation of behavior, as well as moral, ethical and cognitive spheres. Conclusions. It is established that in the formation of destructive consequences an important role is played by conflicting experiences in the system of values and meanings of the professional activity of the serviceman, which are actualized in the situation of threat to life and health of the individual. Accurate assessment and prediction of the impact of combat stress on the personality of the military makes it possible for unit and unit commanders to predict the occurrence of destructive mental states, as well as the dynamics of personnel behavior in extreme conditions and respond adequately to changes in the situation.